(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study aassessed the utilisation of Integrated Payroll and Personnel Information System (IPPIS) and Government Integrated Financial Management and Information System (GIFMIS) as modes of payments in Tertiary Educational institutions in Ogun State, Nigeria with the objectives of investigating the level of awareness of end users on the new government payment policies, and also to determine the relevance of the policies, identify their problems and proffer solutions. The theoretical framework for this study was based on realistic evaluation, a form of theory-based evaluation developed by Pawson and Tilley (1997, 2006), that showcased that outcomes of policies equals mechanism plus concept. Primary data was gathered via close-ended questionnaires. Descriptive statistical tools such as frequencies, percentages in cross tabulations were utilized in analyzing the responses to the questionnaire items. Findings from the study revealed that majority of the respondents have knowledge of the meaning of IPPIS and GIFMIS, and they see the policies as a much needed change in the federal government payment system. Though for now, they delay access to overhead allocations and its utilization, workload seems repetitive and complicated, they debar research donors, make reconciliation of accounts cumbersome, discourage innovations of intellectual properties in Tertiary Educational Institutions, delay contractors payment due to weak communication signals, and seen to be used as a tool to silence unionism, among other findings. It was concluded that contrary to majority belief and apriori expectations, introduction of these policies, though relevant (centralization of government funds) may not curb corruption in federal government financial system, but it will rather get it re-directed elsewhere unless the needful are done. It was therefore recommended that for the policies to work economically, effectively and efficiently there should be timely release of research funds for tertiary educational institutions without sabotage. Adequate monitoring and supervision for checks and balances of the Ministries/Departments/Agencies (MDAs) for effective achievement of the objectives of the new policies are paramount. Furthermore, the new policies should be administered alongside good governance which entails accountability, transparency and probity to ensure adequate and prompt payments to those entitled.